2013
DOI: 10.1007/s00127-013-0695-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of childhood conduct problems in Brazil: systematic review and meta-analysis

Abstract: PurposeThis study aimed to review evidence on the prevalence of and risk factors for conduct problems in Brazil.MethodsWe searched electronic databases and contacted Brazilian researchers up to 05/2012. Studies were included in the review if they reported the prevalence of or risk factors for conduct problems, conduct disorder, or oppositional defiant disorder for 100 + Brazilian children aged ≤18 years, systematically sampled in schools or the community. Prevalence rates and sex differences were meta-analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 58 publications
3
50
1
2
Order By: Relevance
“…It has been generally accepted that boys usually exhibit a higher rate of conduct disorder. However, some studies have been reported in which boys do not always have a higher risk for conduct disorder than girls 14,15,16. These studies raise questions about the sex difference of conduct disorder.…”
Section: Discussionmentioning
confidence: 98%
“…It has been generally accepted that boys usually exhibit a higher rate of conduct disorder. However, some studies have been reported in which boys do not always have a higher risk for conduct disorder than girls 14,15,16. These studies raise questions about the sex difference of conduct disorder.…”
Section: Discussionmentioning
confidence: 98%
“…Although other questionnaire-based studies in Brazil also document very high levels of child behaviour problems [41, 42], there is debate as to whether this reflects overreporting of symptoms by Brazilian parents [42]. It is possible that specific procedures (for example, reading questionnaires to Brazilian parents with less education) or cultural differences in interpreting questionnaire items causes overestimation of children’s behaviour problems in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is unresolved debate about whether Brazilian children actually have such high levels of conduct problems, or whether Brazilian parents tend to overreport problems in short questionnaires (Murray, Anselmi et al. 2013). To help assess this possibility, future studies should include additional measures of child behaviour problems (e.g.…”
Section: Discussionmentioning
confidence: 99%